Parliamentary oversight of governmental work in Arab Maghreb Countries - Benzaghou, Naziha (The International tax journal, 2025)
The parliament, as the legislative authority and representative body of the general administration for the people and the nation, serves as a cornerstone in institutionalizing and guaranteeing constitutional and functional practices. The constitutional framework provides it with tools and mechanisms to perform its oversight duties over governmental activities in several countries. This study focuses on the Arab Maghreb countries, specifically Algeria, Morocco, and Tunisia, analyzing the latest constitutions and internal regulations currently in effect in these parliaments. Parliamentary oversight of state activities in general and governmental actions in particular, holds a vital role in structuring state authority and its constitutional institutions and parliamentary oversight of the executive authority. It is a key constitutional mechanism for ensuring the rule of law. This form of oversight is political in nature and it is exercised by the parliament based on constitutional provisions and characterized by its restriction to members of the legislative authority.